Impact of concomitant dexamethasone dosing schedule on bortezomib‐induced peripheral neuropathy in multiple myeloma. (7th June 2017) - Kumar, Shaji K.; Laubach, Jacob P.; Giove, Thomas J.; Quick, Maureen; Neuwirth, Rachel; Yung, Godwin; Rajkumar, S. Vincent; Richardson, Paul G.
Summary: Peripheral neuropathy (PN) is the most troublesome adverse event associated with the proteasome inhibitor bortezomib. Studies suggest an inflammatory aetiology for bortezomib‐induced PN (BiPN) and it has been hypothesized that reducing inflammation with concomitant dexamethasone may reduce BiPN incidence and/or severity. We retrospectively analysed PN rates from 32 studies (2697 patients with previously untreated multiple myeloma) incorporating bortezomib and differing dexamethasone schedules: partnered dosing (days of and after bortezomib), weekly dosing, and other dosing schedules (e.g. days 1–4, 8–11). Pooled overall PN rates were 45·5%, 63·9%, and 47·5%, respectively, with 5·3%, 11·0%, and 9·6% grade ≥3. Adjusting for potential confounders (age, gender, presence of thalidomide, bortezomib treatment duration), PN rates in patients on partnered dosing schedules appeared lower than in patients on weekly or other dosing schedules. Analyses conducted using patient‐level data suggest that cumulative dexamethasone dose, a potential confounding factor, is unlikely to have influenced the analyses. Findings were similar in a separate pooled analysis excluding data from regimens incorporating thalidomide, when pooled overall PN rates were 50·1%, 63·9%, and 48·3%, respectively, with 4·2%, 11·0%, and 8·6% grade ≥3. These findings suggest that partnered dexamethasone dosing may result in less severe BiPN compared with alternative dexamethasone dosing schedules.